Методы повышения качества данных поляриметрических метеорологических радаров - Рыжков, Александр Васильевич; Мельников, Валерий Михайлович; Зрнич, Душан (Радиотехнические и телекоммуникационные системы; № 2 (2018): Радиотехнические и телекоммуникационные системы, 2018)
An overview of the methods for improving data quality of polarimetric weather radars is presented herein. The issues with data quality addressed in the paper include absolute calibration of radar reflectivity factor Z, absolute calibration of differential reflectivity ZDR, the need for correction for attenuation/differential attenuation in precipitation, and mitigation of partial beam blockage of the radar. Various methodologies are suggested for utilization on weather radars operating at S, C, and X bands. A data-based method for absolute calibration of Z capitalizes on the consistency between Z, ZDR, and specific differential phase KDP in rain. Different techniques for absolute calibration of ZDR are discussed: (1) system internal hardware calibration, (2) “birdbath” calibration with vertically pointing radar, (3) Z – ZDR consistency in light rain, (4) using dry aggregated snow as a natural calibrator for ZDR, and (5) using Bragg scatter as another natural target for calibration. Attenuation and radar beam blockage correction of Z and ZDR is performed using KDP and specific attenuation A which are immune to these factors.